Soluble aromatic polyamides modified by incorporation of 1, 2, 4-triazole and pentadecyl units into the backbone of polymer. Issue 11 (2nd November 2019) - Tamboli, Aslam B.; Bhorkade, Rajesh G.; Kalshetti, Basavraj S.; Ghodake, Shivaji D.; Maldar, Noormahmad N.
Abstract: A new series of soluble aromatic polyamides was synthesized by low temperature solution polycondensation of novel aromatic diamine namely 3, 5-bis-(4′-amino phenyl)-4-(4″-methoxy-2″-pentadecyl phenyl) 1, 2, 4-triazole (VII) with aromatic diacid chlorides, viz. isophthaloyl chloride (IPC) and terephthaloyl chloride (TPC). The aromaticdiamine (VII) was characterized by elemental analysis, FT-IR, NMR ( 1 H, 13 C), and mass spectrometry. Copolyamides were also synthesized by employing various mole proportions of IPC and TPC with diamine (VII). Inherent viscosities of these polyamides were in the range of 0.50–0.65 dL/g in DMAc, indicating formation of moderate to high molecular weight of polyamides. These polyamides showed good solubility in polar aprotic solvents such as N, N-Dimethyl acetamide (DMAc), N-Methyl 2-pyrrolidone (NMP), N, N, Dimethyl formamide (DMF), and Dimethyl sulphoxide (DMSO), which may be due to incorporation of pendant methoxyphenyl moiety with pentadecyl units. The amorphous morphology of polyamides as evidenced by XRD. These polyamides had lower glass transition temperatures; as determined by DSC, compared to the Tg of conventional aromatic polyamides due to internal plasticization effect of long alkyl pentadecyl group. Polymers showed good thermal stability, with initial decomposition temperature above 300 °C.